PELATIHAN DAN PENDAMPINGAN PENULISAN PENELITIAN TINDAKAN KELAS BAGI GURU SMP - perdhani, widya caterube (Jurnal Gramaswara: Jurnal Pengabdian kepada Masyarakat, 2021)
This community service activity aims to train and assist teachers in conducting classroom action research and writing up the results of their research in a scientific paper. Teachers are equipped with fundamental understanding so that they can conduct classroom action research and write scientific papers based on the results of their research. The participants are English teachers in Malang. The activity consists of several stages conducted through both face-to-face meetings and online classes. The results of this activity show that the teachers have a better understanding of conducting and writing down the results of classroom action research, as evidenced by the content of their research reports, which have improved in terms of research background and research methods. In the online sessions, the teachers gave very positive responses, as evidenced by the discussions and active participation among participants and with the service team. This PTK training and mentoring for teachers has significantly contributed positively to improving the quality of learning in the classroom and the quality of teachers in conducting and writing research results. Keywords: teachers; training; classroom action research